1998
DOI: 10.1111/j.1574-695x.1998.tb01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma globulin, Evan's blue, aprotinin A PLA2inhibitor, tetracycline and antioxidants protect epithelial cells against damage induced by synergism among streptococcal hemolysins, oxidants and proteinases: relation to the prevention of post-streptococcal sequelae and septic shock

Abstract: An in vitro model was employed to study the potential role of streptococcal extra-cellular products, rich in streptolysin O, in cellular injury as related to streptococcal infections and post-streptococcal sequelae. Extra-cellular products (EXPA) rich in streptolysin O were isolated from type 4, group A hemolytic streptococci grown in a chemostat, in a synthetic medium. EXPA induced moderate cytopathogenic changes in monkey kidney epithelial cells and in rat heart cells pre-labeled with 3H-arachidonate. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is also of great interest that the cytolytic effects induced by combinations among perforators, oxidants and proteinases can be markedly depressed either by inhibiting the perforator or of the oxidant suggesting that the simultaneous presence of these two agents is absolutely required to induce an irreversible membrane injury (Ginsburg and Sadovnic, 1998). These studies implicate that paradoxically, perhaps, during microbial infections there might occur a deleterious synergistic interaction among microbial and host-derived agonists.…”
Section: The Synergism Concept Of Cellular Injurymentioning
confidence: 96%
See 2 more Smart Citations
“…It is also of great interest that the cytolytic effects induced by combinations among perforators, oxidants and proteinases can be markedly depressed either by inhibiting the perforator or of the oxidant suggesting that the simultaneous presence of these two agents is absolutely required to induce an irreversible membrane injury (Ginsburg and Sadovnic, 1998). These studies implicate that paradoxically, perhaps, during microbial infections there might occur a deleterious synergistic interaction among microbial and host-derived agonists.…”
Section: The Synergism Concept Of Cellular Injurymentioning
confidence: 96%
“…The concept that tissue damage initiated during and following microbial invasion, might be caused by interaction between several pro-inflammatory agonists, had emerged form observations on the pathophysiology of tissue damage induced by catalase-negative bacteria (streptococci, clostridiae) (Ginsburg, 1972(Ginsburg, , 1996(Ginsburg, , 1998Ginsburg et al, 1995Ginsburg et al, , 1998Ginsburg and Sadovnic, 1998). Already by 1959, it had been shown that tumour cells injured by the membrane-perforating toxin, steptolysin S (SLS), were rapidly disintegrated by non-cytolytic amounts of a cysteine proteinase derived from streptococci (Ginsburg, 1972).…”
Section: The Synergism Concept Of Cellular Injurymentioning
confidence: 99%
See 1 more Smart Citation